Status of ICT Application/Library Automation in Selected Government Libraries in Delhi: A Study - Sanjay, Kumar; Singh, K. P. (Journal of Information and Knowledge, 2024)
The application of Information and Communication Technology (ICT) in libraries and the automation/computerisation of libraries play a vital role in providing timely and effective information services to users. This paper examines the status of libraries attached to select ministries of the Government of India. This study examines the status of automation, availability of e-resources and use of IT in the select libraries.